Outer-Tuning: an Ontology-based Extensible Framework for Supporting Database Automatic Tuning - Marins, Raphael; Pereira de Oliveira, Rafael; Hermann Haeusler, Edward; Lifschitz, Sérgio; Schwabe, Daniel; Almeida, Ana Carolina (Journal of Information and Data Management, 2021)
This paper presents the Outer-Tuning framework, which aims to support the (semi) automatic tuning of relational database systems through a domain-specific ontology. Ontologies have shown themselves to be increasingly promising, adding semantics and standardizing the different terms used in a domain. Thereby, our framework seeks to explain and make explicit the tuning heuristics reasoning while enabling the evaluation of new ontology-inferred methods. In this paper we focus on the main aspects of the Outer-Tuning component-based architecture. We also give an overview of our tool in practice. Finally, we show two useful extensions, concerning new DBMSs and a way of dockerizing into a container.